2017
DOI: 10.1080/19420862.2017.1389364
|View full text |Cite
|
Sign up to set email alerts
|

Safety testing of monoclonal antibodies in non-human primates: Case studies highlighting their impact on human risk assessment

Abstract: Monoclonal antibodies (mAbs) are improving the quality of life for patients suffering from serious diseases due to their high specificity for their target and low potential for off-target toxicity. The toxicity of mAbs is primarily driven by their pharmacological activity, and therefore safety testing of these drugs prior to clinical testing is performed in species in which the mAb binds and engages the target to a similar extent to that anticipated in humans. For highly human-specific mAbs, this testing often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 68 publications
(85 reference statements)
0
36
0
7
Order By: Relevance
“…This threshold is not unreasonably high, as our analysis of a low-dose SHIV challenge study below showed that a few macaques got infected in spite of serum bnAb levels corresponding to 95–99% in vitro neutralization of the challenge pseudovirus [ 21 ]. In the ongoing Phase 2b VRC01 clinical trials, the minimum VRC01 in vivo serum concentrations are predicted to be 5–16 μg/ml [ 52 ]. Based on this, we chose the target minimum concentration of 10 μg/ml total for our modeling of Abs, individually or in combinations.…”
Section: Resultsmentioning
confidence: 99%
“…This threshold is not unreasonably high, as our analysis of a low-dose SHIV challenge study below showed that a few macaques got infected in spite of serum bnAb levels corresponding to 95–99% in vitro neutralization of the challenge pseudovirus [ 21 ]. In the ongoing Phase 2b VRC01 clinical trials, the minimum VRC01 in vivo serum concentrations are predicted to be 5–16 μg/ml [ 52 ]. Based on this, we chose the target minimum concentration of 10 μg/ml total for our modeling of Abs, individually or in combinations.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been applied to a variety of IgG compounds as well as other therapeutic proteins 137 . There are very recent attempts at analyzing highly concentrated formulations using bioanalytical methods, however these methods are not used throughout industry 138,139 .…”
Section: Formulation Considerationsmentioning
confidence: 99%
“…The safety of therapeutic antibodies must be evaluated in a preclinical setting prior to human trials. This important step of drug development usually necessitates that the clinical candidate cross-reacts to the appropriate preclinical animal species chosen for toxicology ( 81 , 82 ). To ensure our lead candidates can meet this stringent design goal, we frequently incorporate the orthologous antigen from the toxicology species into our immunization protocols.…”
Section: Strategies For Steering Antibody Repertoiresmentioning
confidence: 99%